Editorial Volume 4, Issue 2 - Ciorstan J. Smark (Australasian Accounting, Business and Finance Journal, 2010)
AABFJ acknowledges the field of business research as a socially constructed one (Arrington & Francis 1989; Hines 1988) and acknowledges that a rich diversity of views and forms of expression exist within this field of business research. AABFJ has already published alternate forms of discourse such as dialogues (Hong 2007) and Poetry (Lenthen 2008). In response to calls for greater diversity in expression within business research, (Williams 2001) to encourage a broader range of researchers and enhance contact between disciplines (Reiter & Williams 2002) AABFJ hopes to broaden business research conversation by also accepting submissions of shorter research notes, critiques and responses to previously published articles and also book reports. The AABFJ website will be updated shortly to provide further details.